Photodegradation of Reactive Blue 4 Using Suspension of Anatase Titanium Dioxide and Corn Cob - Shariena, Shamsul Bahari; Lian, Yuen Mei; Ros Azlinawati, Ramli; Ling, Lee Siew (Trans Tech Publications Ltd, 2022)
Textile dyeing often employs reactive dyes. The dye wastewater contains hazardous materials and is toxic to humans and the environment. Photodegradation using a semiconductor photocatalyst is a promising alternative approach for water purification and wastewater treatment. However, the photocatalyst’s low adsorption ability is a problem in the photocatalysis process. To compensate for this shortcoming, photocatalyst content must be combined with an adsorbent. Raw corn cob and titanium dioxide (TiO2) were used in this photocatalysis. Due to a synergistic impact, raw corn cob’s ability to adsorb and titanium dioxide’s ability to photodegrade organic pollutants from water bodies is expected to boost the removal performance. The degradation of Reactive Blue 4 (RB4) as a targeted dye was carried out in this research using a suspended mixture of commercial anatase TiO2 and raw corn cob under UV light. The effect of initial pH solution, initial dye concentration and contact time, TiO2-corn cob dosages, and the influence of other pollutants were investigated as factors influencing photodegradation-adsorption of RB4. The high removal rate of RB4 was obtained at a low pH of 2 and RB4 concentration of 40 ppm. The increased dose of TiO2-corn cob improved the RB4 dye removal performance. In conclusion, combining photodegradation and adsorption systems as a hybrid treatment method resulted in a synergistic increase in the efficiency of RB4 removal.